Strategic Personnel Management within Innovational Development of Companies - DANILINA, Elena I.; MINGALEVA, Zhanna A.; MALIKOVA, Yana I. (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
Nowadays the key factor of competitiveness is a continuous process of innovations. The level of innovations in a company is influenced by various factors. The system of strategic personnel management, including the one in the area of innovations, holds a special place among them. The article researches statistical interrelations between the tempos of innovational development of enterprises, system of innovations incentive, and general system of personnel reward. Using methods of institutional analysis, the authors researched strategies of personnel management in the area of innovational activity of novelty applied in Russian companies. It is statistically shown that tempos of the companies’ innovational development depend on the system of incentives of the employees’ innovational activity. It is confirmed that the innovational development is based on the system of personnel incentives for innovations, strong corporate culture, and correctly chosen strategies of personnel management.
Keywords: strategic personnel management; innovational development; motivation; incentive system of innovations; corporate culture